Secondary Non-Response to Biologic Treatment in Patients with Severe Asthma - Mobayed H; Al-Nesf M; Ibrahim T; Aqel S; Al-Ahmad M; Bousquet J (Journal of Asthma and Allergy)
Hassan Mobayed,1,* Maryam Al-Nesf,1,* Tayseer Ibrahim,1 Sami Aqel,1 Mona Al-Ahmad,2,3 Jean Bousquet4– 6 1Allergy and Immunology Division, Department of Medicine, Hamad Medical Corporation, Doha, Qatar; 2Department of Microbiology, College of Medicine, Kuwait University, Kuwait City, Kuwait; 3Al‐Rashed Allergy Center, Ministry of Health, Kuwait City, Kuwait; 4Macvia France, Montpellier, France; 5Hospital Charité, Institute of Allergology, Universitätsmedizin Berlin, Humboldt-Universität Zu Berlin, Berlin, Germany; 6Department of Dermatology and Allergy, Comprehensive Allergy Center, Berlin Institute of Health, Berlin, Germany*These authors contributed equally to this workCorrespondence: Hassan Mobayed, Allergy and Immunology Division, Department of Medicine, Hamad Medical Corporation, Doha, Qatar, Tel +97455443313, Email hmobayedh@hamad.qa Maryam Al-Nesf, Allergy and Immunology Division, Department of Medicine, Hamad Medical Corporation, Doha, Qatar, Tel +97455820125, Email mariamali@hamad.qaAbstract: Biologic therapies have revolutionized the management of severe asthma (SA), offering significant symptom control and reduced exacerbations for many patients. However, up to 25% of individuals do not show satisfactory responses to these treatments and are categorized as non-responders. Definitions of response and primary non-response to biologics in SA are well-established. In secondary nonresponse, patients show initial response to biological treatment in the first 6– 12 months but later lose asthma control, and in SA this phenomenon remains undefined and unstudied in literature. We present 4 cases of severe asthma treated with different biologic agents. All patients demonstrated significant clinical improvement during the first 12 months of therapy but followed by a gradual loss of asthma control, indicative of secondary nonresponse. We discuss the clinical features, potential mechanisms, and implications of secondary nonresponse to biologics in severe asthma, highlighting an unmet need for further research to define this phenomenon and guide future therapeutic strategies.Keywords: severe asthma, biological treatment of severe asthma, non-response to biologics in severe asthma, secondary nonresponse to biologics in severe asthma, type 2 severe asthma